Using the measure of patient centred communication to assess oncology consultations. (1st April 2011) - Absolom, K; Hector, C; Campbell, L; Eng, S; Taylor, S; Takeuchi, E; Warrington, L; Ziegler, L; Velikova, G
Abstract : Abstract: Numerous instruments to assess doctor-patient communication have been developed to date. The Measure of Patient Centred Communication (MPCC)1 was created for use in primary care and measures three components of communication (1) Exploring the disease (2) Understanding the whole person (3) Finding common ground. In ongoing research we are exploring the suitability of the MPCC for assessing chemotherapy review consultations. Here we present our preliminary experiences of using this coding framework. Methods: Between October 2009 and November 2010, 496 outpatient consultations with 124 patients were audio-recorded at St James' Institute of Oncology, Leeds. All patients were receiving chemotherapy for either advanced colorectal (n=49), gynaecological (n=48) or breast cancer (n=27). A team of eight coders are analysing recordings using both the MPCC and content analyses. Results: Preliminary findings suggest the MPCC can be applied to oncology consultations. The coding team have reached agreement on how to code key issues discussed by patients and doctors including symptoms of the cancer, side effects of treatment, questions about prognosis, treatment decision making and the doctors' explanations about cancer status throughout chemotherapy cycles. Conclusions: The MPCC may be a useful tool for examining patient-centredness in oncology. Future work will explore the value of the MPCC in assessing the impact of routinely collecting and feeding back patient reported outcome (PRO) data to oncologists. The MPCC will be used to assess if training oncologists to interpret and use the PRO data improves patient-centred care in consultations.